O uso do Role Playing Game (RPG) como ferramenta didática no ensino de Ciências - Ingrid Miranda de Abreu Coelho (2017)
Educational games are a viable tool for teaching science that allows the development of teamwork skills, learning with mistakes, creativity among others. Therefore, the objective of this research was to develop, apply and analyze a educational game in the format of a Role Playing Game (RPG) to teach science approaching brazilian biome for elementary school. RPG is characterized by role playing and allow the students to visit, in their imagination, the biome and get to know and treasure those environments. The game was applied with a 6th grade class in elementary school and to collect data were utilized field notebooks, audio recording and interviews with teacher and students. The data was analised using a microgenetic approach and presented as a game application report, with emphasis on: the difficulties that the students showed while playing the game; the interaction between students and the material as a cultural amplifier; the events that allow to confirm that the game enables the productive disciplinary engagement. The results show that the game is an efficient mediator between knowledge and the students, favouring learning, developing skills intrinsic to the act of playing and allowing productive disciplinary engagement.